DAYA IKAT FRAMEWORK AGREEMENT TERHADAP PIHAK KETIGA(STUDI KASUS TERHADAP NOTA KESEPAKATAN ANTARA INDONESIA DAN SINGAPURA MENGENAI PENGEMBANGAN KAWASAN EKONOMI KHUSUS DI PULAU BATAM, BINTAN DAN KARIMUN) - Rudi Natamihardja (Universitas Lampung, 2007)
Cooperation between Indonesia and Singapore concerning special economic kewasan Batan-Bintan-Karimun, Special Economic Zone (BBK-SEZ) is a bilateral agreement in the form of frame work agrement. Because of its open verdrag (open), then it is possible for a third party becomes a participant in the agreement. Keywords: Frame Work Agreement, a Special Economic Zone